Polystyrene-based hard carbon microspheres as well as preparation method and application thereof

The preparation of polystyrene-based hard carbon microspheres through microsuspension polymerization solves the problem of difficult balance between sodium storage capacity and first effect of hard carbon anode materials, achieves high compaction density and low specific surface area, and improves the performance of lithium/sodium ion batteries.

CN119683598AActive Publication Date: 2025-03-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311234507.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

It is difficult to balance hard carbon negative electrode materials between sodium storage capacity and first effect. Traditional preparation methods lead to low compaction density and large specific surface area, which affects battery performance.

Method used

Polystyrene-based hard carbon microspheres were prepared by microsuspension polymerization. Through pre-oxidation and carbonization steps, the average particle size and specific surface area of ​​the material were controlled, and the compaction density and pore structure of the material were increased.

Benefits of technology

A higher compaction density and lower specific surface area are achieved, and the sodium storage capacity and first effect are improved. The initial capacity reaches no less than 310.1mAh/g, and the first effect is between 91 and 96%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683598A_ABST
    Figure CN119683598A_ABST
Patent Text Reader

Abstract

The invention discloses polystyrene-based hard carbon microspheres as well as a preparation method and application thereof. And carrying out oxidation-carbonization treatment on the polymer microspheres obtained by micro-suspension polymerization to obtain the hard carbon microspheres capable of being used for the negative electrode of the battery. The obtained microspheres maintain the morphology of the polymer precursor, and the skeleton structure of the microspheres shrinks, so that the carbon microspheres with higher compaction density and lower specific surface area can be obtained. In addition, the release of the pore-foaming agent provides a rich pore channel structure for the carbon microspheres, and is beneficial to shortening the diffusion distance of substances or charges and better exposing active sites while the specific surface of the carbon microspheres is not obviously improved, so that the electrode capacity is improved while the high first efficiency of the electrode is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to polystyrene-based hard carbon microspheres and a preparation method and application thereof, belonging to the field of battery materials. Background Art

[0002] Energy storage / lithium battery / sodium battery introduction: The development of energy storage technology is crucial for balancing electricity supply and demand, integrating renewable energy, improving grid stability and responding to energy demand. It helps to optimize the energy structure and reduce carbon emissions. Lithium batteries have high energy density and are an important part of energy storage technology. They have been widely used in daily life. However, limited lithium resources, safety hazards of lithium batteries, and high energy loss at low temperatures limit the wider application of lithium batteries. Compared with lithium batteries, sodium batteries have more abundant raw material resources and can significantly reduce energy loss at low temperatures. They can be used as a good supplement to lithium batteries in practical applications and are considered to be energy storage batteries with great potential. Both energy storage technologies play an important role in achieving energy sustainability, reducing carbon emissions and improving grid stability.

[0003] Hard carbon can not only be used as the negative electrode of lithium-ion batteries, but is also considered to be one of the most promising negative electrode materials for sodium-ion batteries. It has received increasing attention and research in the past 10 years. At present, the source of hard carbon is mainly obtained from biomass, petrochemical raw materials and polymer resins through high-temperature pyrolysis. The structure and properties of the precursor have a significant impact on the performance of the obtained hard carbon. CN 112397715 B discloses a hard carbon material, a preparation method thereof and a sodium ion battery, wherein a coal-based material and a sugar are mixed and cross-linked as a hard carbon precursor, and after acid washing and water washing to remove impurities, the degree of cross-linking is increased and the specific surface area is reduced by extrusion reaction, but the process produces acidic wastewater and the resulting hard carbon has a low density, so the degree of cross-linking needs to be increased by extrusion, and the particle size needs to be controlled by screening; Facile regulation of carbon frameworks from microporous to lowporous via molecular crosslinker design and enhanced Na storage. Carbon 2020, 167, 896-905, in which the Scholl reaction is used to cross-link polystyrene to reduce the generation of micropores and reduce the specific surface area, thereby reducing the ineffective decomposition of the electrolyte and the ineffective formation of the solid electrolyte interface film (SEI), and improving the initial efficiency, but the precursor morphology cannot be maintained during the cross-linking process, and post-treatment such as grinding and screening is required, and the low-porosity hard carbon prepared by this method exhibits a lower capacity (270 mAh / g); CN 102386384 B discloses a spherical hard carbon lithium-ion battery negative electrode material and a preparation method thereof, wherein a hard carbon precursor is mixed with a coating material and spray granulated to obtain an outer-wrapped precursor, which is then pyrolyzed to obtain hard carbon. The method uses a ball mill, a mixer and a spray granulator, and the obtained hard carbon balls have a large volume, a low density and a low specific capacity. Summary of the invention

[0004] The technical problem to be solved by this application is: the performance of hard carbon negative electrode needs to consider the balance between sodium storage capacity and first efficiency. On the one hand, reducing the specific surface area and reducing low defects and micropores will help improve the first efficiency and stabilize the voltage platform of lithium / sodium ion batteries; on the other hand, reducing micropores and reducing the specific surface will slow down ion diffusion and transmission and reduce the sodium storage capacity.

[0005] The irregular or overly regular morphology of traditional hard carbon leads to low compaction density and low battery energy density. The polystyrene-based resin prepared by the micro-suspension polymerization method of the present invention is pre-oxidized and carbonized to obtain carbon spheres with an average particle size of 3 to 15 μm. The lower specific surface area and more compact compaction density make the material have better initial effect. At the same time, due to the addition of porogens during the polymerization process, the microspheres contain pores, which are conducive to ion diffusion and transmission and increase of sodium storage capacity.

[0006] This application adopts the following technical solutions:

[0007] A method for preparing polystyrene-based hard carbon microspheres comprises the following steps:

[0008] S1, adding emulsifier, divinylbenzene, styrene, porogen and initiator into water to form a suspension;

[0009] S2, heating the suspension formed in step S1 to react and obtain polymer spheres;

[0010] S3, pre-oxidizing and carbonizing the polymer spheres obtained in step S2 to obtain the polystyrene-based hard carbon microspheres.

[0011] Optionally, in step S1, the emulsifier is selected from at least one of polyvinyl alcohol, OP-10, Tween, Span, sodium gluconate, and sodium alginate.

[0012] Optionally, in step S1, the mass content ratio of the emulsifier to styrene is 0.03 to 0.15:1.

[0013] Optionally, in step S1, the porogen is selected from C 6 ~C 15 At least one of the liquid alkanes.

[0014] Optionally, the porogen is selected from at least one of dodecane, tridecane and tetradecane.

[0015] Optionally, in step S1, the mass content ratio of the porogen to styrene is 0.1 to 2.57:1.

[0016] Optionally, in step S1, the initiator is selected from at least one of benzoyl peroxide, azobisisobutyronitrile, and lauryl peroxide.

[0017] The initiator is a lipophilic free radical initiator.

[0018] Optionally, in step S1, the mass content ratio of the initiator to styrene is 0.01 to 0.1:1.

[0019] Optionally, in step S1, the weight ratio of divinylbenzene to styrene is 0.1 to 1.5:1.

[0020] Optionally, in step S1, the mass content ratio of water to styrene is 3 to 15:1.

[0021] Optionally, in step S2, the heating reaction includes stage I, stage II, and stage III.

[0022] The reaction conditions of the stage I are: reaction temperature of 65-72°C, reaction time of 1h-4h;

[0023] The reaction conditions of the stage II are: reaction temperature of 72-78°C, reaction time of 3h-12h;

[0024] The reaction conditions of the stage III are: reaction temperature of 82-95° C., and reaction time of 8-16 h.

[0025] Optionally, a stage II-1 is further included between the stage II and the stage III, and the reaction conditions of the stage II-1 are: reaction temperature is 78 to 82° C., and reaction time is 0.2 h to 0.8 h.

[0026] Optionally, in step S3, the pre-oxidation comprises: pre-oxidizing the polymer spheres with an oxidant; or

[0027] The polymer spheres are pre-oxidized in an oxidizing atmosphere;

[0028] Wherein, the oxidizing atmosphere is oxygen or air.

[0029] Optionally, in step S3, the oxidant is selected from at least one of hydrogen peroxide, concentrated nitric acid, concentrated sulfuric acid, and ferric nitrate.

[0030] Optionally, in step S3, the weight ratio of the polymer spheres to the oxidant is 1:0.5-4.

[0031] Optionally, in step S3, the pre-oxidation conditions are:

[0032] The pre-oxidation is carried out under air conditions, with a pre-oxidation temperature of 60 to 300°C and a pre-oxidation time of 6 to 10 hours.

[0033] Optionally, the heating rate of the pre-oxidation is 3-10° C. / min.

[0034] Optionally, the carbonization conditions are:

[0035] The carbonization process is carried out under an inert gas atmosphere, with a carbonization temperature of 700 to 1600° C., a carbonization time of 0.5 to 10 hours, and a heating rate of 1 to 15° C. / min.

[0036] Optionally, the inert gas atmosphere is selected from at least one of nitrogen, helium and argon.

[0037] According to another aspect of the present application, a polystyrene-based hard carbon microsphere is provided, wherein the polystyrene-based hard carbon microsphere is prepared by the preparation method according to any one of claims 1 to 6.

[0038] Optionally, the average particle size of the polystyrene-based hard carbon microspheres is 3 to 15 um.

[0039] Optionally, the compacted density of the polystyrene-based hard carbon microspheres is 1.1 to 1.6 g / cm 3 .

[0040] Optionally, the specific surface area of ​​the polystyrene-based hard carbon microspheres is 2 to 25 m 2 / g.

[0041] Optionally, the crystallite interlayer spacing of the polystyrene-based hard carbon microspheres is 0.374 to 0.421 nm.

[0042] According to another aspect of the present application, an electrode material is also provided, wherein the electrode material comprises the above-mentioned polystyrene-based hard carbon microspheres.

[0043] According to another aspect of the present application, there is also provided application of the above-mentioned electrode material in a lithium ion battery or a sodium ion battery.

[0044] The beneficial effects of this application include:

[0045] The present invention has developed a simple and easy-to-scale method for preparing polystyrene-based carbon spheres. Due to the uneven size distribution of micro-suspension polymer particles and the smaller specific surface area of ​​the spheres, a higher compaction density and a lower specific surface area can be obtained. At the same time, the pores in the microspheres are conducive to increasing the capacity. The average particle size before carbonization is 4 to 30 μm, and after carbonization is 3 to 15 μm. The compaction density of the hard carbon prepared by this method is 1.1 to 1.6 g / cm 3 , specific surface area 2~25m 2 / g, microcrystalline interlayer spacing of 0.374 ~ 0.421nm, with high sodium storage capacity and high initial efficiency, the initial capacity is not less than 310.1mAhg -1 The initial effect is between 91% and 96%. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is the nitrogen physical adsorption-desorption curve of the sample in Example 1.

[0047] Figure 2 The scanning electron microscope photograph of the sample in Example 1 is shown with a scale of 1 μm. DETAILED DESCRIPTION

[0048] The present invention is further described below by means of specific implementation methods. The following examples are specific implementation methods of the present invention, but the implementation methods of the present invention are not limited to the following examples.

[0049] According to one implementation of the present application:

[0050] The preparation steps of polystyrene-based hard carbon microspheres include:

[0051] Step 1: In 60g of 1% polyvinyl alcohol aqueous solution, stir and add a mixed solution of 12.6g of divinylbenzene, 7.68g of styrene, 15g of tridecane and 0.18g of benzoyl peroxide after removing the inhibitor, heat to 70℃ for reaction for 2h, then heat to 75℃ for reaction for 4h, then heat to 80℃ for reaction for 0.5h, and finally heat to 90℃ for reaction for 11h.

[0052] Step 2: After washing and drying, the obtained styrene-diethylenebenzene copolymer is pre-oxidized by heating to 250°C at 3°C / min and maintaining for 10 hours in air.

[0053] The temperature was slowly raised to 250°C for oxidative crosslinking and evaporation of the porogen.

[0054] Step 3: The pre-oxidized sample is heated to 1400° C. at a heating rate of 5° C. / min under a nitrogen atmosphere and maintained for 2 hours to obtain the polystyrene-based hard carbon microspheres.

[0055] Example 1

[0056] Step 1: In 70g of 0.3% polyvinyl alcohol aqueous solution, stir and add a mixed solution of 0.7g of divinylbenzene, 7g of styrene, 0.7g of tridecane and 0.07g of benzoyl peroxide after removing the inhibitor, heat to 70℃ and react for 2h, then heat to 75℃ and react for 4h, and then heat to 90℃ and react for 11h.

[0057] Step 2: After washing and drying, the obtained styrene-diethylenebenzene copolymer is pre-oxidized by heating to 250°C at 3°C / min and maintaining for 10 hours in air, and then slowly heated to 250°C for oxidative crosslinking and evaporation of the porogen.

[0058] Step 3: The pre-oxidized sample was heated to 1400° C. at a heating rate of 5° C. / min under a nitrogen atmosphere and maintained for 2 h to obtain a sample.

[0059] Figure 1 This is a nitrogen physical adsorption-desorption curve of the sample in Example 1. From this figure, it can be seen that the sample has a small specific surface area.

[0060] Figure 2 The scanning electron microscope photograph of the sample in Example 1 is shown with a scale of 1 μm. From this picture, it can be seen that the sample has good sphericity and a smooth surface.

[0061] Example 2

[0062] In 105g of 1% polyvinyl alcohol aqueous solution, a mixed solution of 10.5g of divinylbenzene, 7g of styrene, 18g of tetradecane and 0.21g of azobisisobutyronitrile with the inhibitor removed was stirred and added, and the temperature was raised to 72°C for reaction for 1h, then raised to 78°C for reaction for 3h, and then raised to 95°C for reaction for 8h; after washing and drying, the obtained styrene divinylbenzene copolymer was pre-oxidized by heating to 250°C at 3°C / min and maintaining for 10h under oxygen conditions; the pre-oxidized sample was heated to 1400°C at a heating rate of 5°C / min in a helium atmosphere and maintained for 2h to obtain a sample.

[0063] Example 3

[0064] 0.1 g of OP-10 was added to 30.42 g of 1% Span aqueous solution, stirred and a mixed solution of 2 g of divinylbenzene from which the inhibitor was removed, 10.14 g of styrene, 5 g of dodecane and 0.18 g of lauryl peroxide was added, the temperature was raised to 70°C for reaction for 2 h, the temperature was raised to 75°C for reaction for 4 h, and the temperature was further raised to 90°C for reaction for 11 h; after washing and drying, the obtained styrene divinylbenzene copolymer was pre-oxidized by heating to 300°C at 3°C / min and maintaining for 10 h under air conditions; the pre-oxidized sample was heated to 1400°C at a heating rate of 5°C / min under argon atmosphere and maintained for 10 h to obtain a sample.

[0065] Example 4

[0066] 0.05g OP-10 and 0.03g Tween were added to 30.42g 0.1% sodium gluconate aqueous solution, stirred and added with 2g divinylbenzene, 10.14g styrene, 5g tridecane and 0.18g benzoyl peroxide mixed solution after removing the inhibitor, heated to 70°C for reaction for 2h, then heated to 75°C for reaction for 4h, and then heated to 90°C for reaction for 16h; after washing and drying, 30g resin was mixed with 15g ferric nitrate nonahydrate, heated to 60°C for pre-oxidation; after washing and drying, the pre-oxidized sample was heated to 1600°C at a heating rate of 15°C / min in a nitrogen atmosphere and maintained for 0.5h to obtain a sample.

[0067] Example 5

[0068] In 70g of 1% sodium alginate aqueous solution, stir and add a mixed solution of 10.5g of divinylbenzene, 7g of styrene, 12g of tridecane and 0.7g of azobisisobutyronitrile from which the inhibitor has been removed, heat to 70°C for reaction for 2h, then heat to 75°C for reaction for 4h, and then heat to 92°C for reaction for 2h; after washing and drying, 15g of the resin is mixed with 60g of hydrogen peroxide, heated to 80°C for pre-oxidation; after drying, the pre-oxidized sample is heated to 700°C at a heating rate of 1°C / min under a nitrogen atmosphere and maintained for 2h to obtain a sample.

[0069] Example 6

[0070] In 70g of 1% sodium alginate aqueous solution, stir and add a mixed solution of 10.5g of divinylbenzene, 7g of styrene, 12g of tridecane and 0.7g of azobisisobutyronitrile from which the inhibitor has been removed, heat to 70°C for reaction for 2h, then heat to 75°C for reaction for 4h, and then heat to 91°C for reaction for 4h; after washing and drying, 15g of the resin is mixed with 30g of concentrated sulfuric acid and 10g of concentrated nitric acid, heated to 80°C for pre-oxidation; after drying, the pre-oxidized sample is heated to 900°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 1h to obtain a sample.

[0071] Example 7

[0072] In 70g of 1% Span aqueous solution, stir and add a mixed solution of 10.5g of divinylbenzene, 7g of styrene, 12g of tridecane and 0.7g of benzoyl peroxide from which the inhibitor has been removed, heat to 65°C for reaction for 4h, then heat to 72°C for reaction for 12h, and then heat to 82°C for reaction for 16h; after washing and drying, 15g of the resin is mixed with 30g of concentrated sulfuric acid and 10g of concentrated nitric acid, heated to 80°C for pre-oxidation; after drying, the pre-oxidized sample is heated to 900°C at a heating rate of 5°C / min in a nitrogen atmosphere and maintained for 1h to obtain a sample.

[0073] Comparative Example 1

[0074] 0.1g of Tween was added to 60g of 1% polyvinyl alcohol aqueous solution, stirred and a mixed solution of 12.6g of divinyl benzene, 7.68g of styrene, 15g of tridecane and 0.18g of benzoyl peroxide from which the inhibitor was removed was added, the temperature was raised to 70°C for reaction for 2h, the temperature was raised to 75°C for reaction for 4h, and the temperature was further raised to 90°C for reaction for 11h; after washing and drying, the obtained styrene divinyl benzene copolymer was pre-oxidized by heating to 250°C at 3°C / min and maintaining for 10h under air conditions; the pre-oxidized sample was heated to 1400°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 2h to obtain a sample.

[0075] Comparative Example 2

[0076] 0.1 g of sodium alginate was added to 60 g of 1% OP-10 solution, and the mixture was stirred and added with 12.6 g of divinyl benzene from which the polymerization inhibitor was removed, 7.68 g of styrene, 15 g of tridecane and 0.18 g of benzoyl peroxide mixed solution. The mixture was heated to 70° C. for reaction for 2 h, then heated to 75° C. for reaction for 4 h, and then heated to 90° C. for reaction for 11 h. After washing and drying, the obtained styrene divinyl benzene copolymer was pre-oxidized by heating the mixture to 250° C. at a rate of 3° C. / min and maintaining the mixture for 10 h in air. The pre-oxidized sample was heated to 1800° C. at a rate of 5° C. / min in a nitrogen atmosphere and maintained for 2 h to obtain a sample.

[0077] Comparative Example 3

[0078] In 70g of 0.3% polyvinyl alcohol aqueous solution, stir and add a mixed solution of 0.7g of divinylbenzene, 7g of styrene, 0.7g of tridecane and 0.07g of benzoyl peroxide from which the inhibitor has been removed, heat to 85°C and react for 4h, then heat to 96°C and react for 11h; after washing and drying, 30g of the resin is mixed with 15g of ferric nitrate nonahydrate, heated to 50°C for pre-oxidation; after washing and drying, the pre-oxidized sample is heated to 1800°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 2h to obtain a sample.

[0079] Comparative Example 4

[0080] In 70g of 1% sodium alginate aqueous solution, stir and add a mixed solution of 12g of divinylbenzene, 6g of styrene, 1g of tridecane and 0.7g of azobisisobutyronitrile from which the inhibitor has been removed, heat to 70°C for reaction for 2h, and then heat to 90°C for reaction for 4h; after washing and drying, 15g of the resin is mixed with 110g of concentrated sulfuric acid and 10g of concentrated nitric acid, heated to 80°C for pre-oxidation; after drying, the pre-oxidized sample is heated to 900°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 1h to obtain a sample.

[0081] Test Example 1

[0082] The samples obtained in Examples 1, 2, 3, 4, 5, 6, and 7 and Comparative Examples 1, 2, 3, and 4 were tested and inspected. The results are shown in Table 1.

[0083] The specific surface area was measured by nitrogen physical adsorption using Quantachrome equipment; the particle size distribution was measured by Malvern 2000 laser particle size analyzer and water phase ultrasound for 2 min; and the interplanar spacing was the interplanar spacing corresponding to the (002) peak in XRD.

[0084] In the battery test, 1M NaClO4 in ethyl carbonate and ethylene fluoride carbonate (1:1) was used as the electrolyte, and the working electrode was composed of active material, Ketjen black and polyvinyl difluoride in a mass ratio of 7:2:1. The mass loading of active material in the electrode was about 1mg cm-2. Constant current charge and discharge tests were carried out in the range of 0.01-3V.

[0085]

[0086]

[0087] It can be seen that the method of the present application can obtain a higher compaction density and a lower specific surface area due to the uneven size distribution of micro-suspended polymer particles and the smaller specific surface area of ​​the spherical shape. At the same time, the pores in the microspheres are conducive to improving the capacity.

[0088] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing polystyrene-based hard carbon microspheres, characterized in that: The following steps are involved: S1, adding emulsifier, divinylbenzene, styrene, porogen and initiator into water to form a suspension; S2, heating the suspension formed in step S1 to react and obtain polymer spheres; S3, pre-oxidizing and carbonizing the polymer spheres obtained in step S2 to obtain the polystyrene-based hard carbon microspheres.

2. The preparation method according to claim 1, characterized in that: In step S1, the emulsifier is selected from at least one of polyvinyl alcohol, OP-10, Tween, Span, sodium gluconate, and sodium alginate; Preferably, in step S1, the mass content ratio of the emulsifier to styrene is 0.03-0.15:

1.

3. The preparation method according to claim 1, characterized in that: In step S1, the porogen is selected from C6 to C 15 At least one of the liquid alkanes; Preferably, in step S1, the mass content ratio of the porogen to styrene is 0.1 to 2.57:1; Preferably, in step S1, the initiator is selected from at least one of benzoyl peroxide, azobisisobutyronitrile, and lauryl peroxide; Preferably, in step S1, the mass content ratio of the initiator to styrene is 0.01 to 0.1:1; Preferably, in step S1, the weight ratio of divinylbenzene to styrene is 0.1 to 1.5:1; Preferably, in step S1, the mass content ratio of water to styrene is 3 to 15:

1.

4. The preparation method according to claim 1, characterized in that: In step S2, the heating reaction includes stage I, stage II, and stage III; The reaction conditions of the stage I are: reaction temperature of 65-72°C, reaction time of 1h-4h; The reaction conditions of the stage II are: reaction temperature of 72-78°C, reaction time of 3h-12h; The reaction conditions of the stage III are: reaction temperature of 82-95° C., and reaction time of 8-16 h. Optionally, a stage II-1 is further included between the stage II and the stage III, and the reaction conditions of the stage II-1 are: reaction temperature is 78 to 82° C., and reaction time is 0.2 h to 0.8 h.

5. The preparation method according to claim 1, characterized in that: In step S3, the pre-oxidation comprises: pre-oxidizing the polymer spheres with an oxidant; or The polymer spheres are pre-oxidized in an oxidizing atmosphere; Wherein, the oxidizing atmosphere is oxygen or air; Preferably, in step S3, the oxidant is selected from at least one of hydrogen peroxide, concentrated nitric acid, concentrated sulfuric acid, and ferric nitrate; Preferably, in step S3, the weight ratio of the polymer spheres to the oxidant is 1:0.5-4; Preferably, in step S3, the pre-oxidation conditions are: The pre-oxidation is carried out under air conditions, with a pre-oxidation temperature of 60 to 300°C and a pre-oxidation time of 6 to 10 hours. Optionally, the heating rate of the pre-oxidation is 3-10° C. / min.

6. The preparation method according to claim 1, characterized in that: The carbonization conditions are: The carbonization process is carried out under an inert gas atmosphere, with a carbonization temperature of 700 to 1600° C., a carbonization time of 0.5 to 10 hours, and a heating rate of 1 to 15° C. / min. Optionally, the inert gas atmosphere is selected from at least one of nitrogen, helium and argon.

7. A polystyrene-based hard carbon microsphere, characterized in that: The polystyrene-based hard carbon microspheres are prepared by the preparation method according to any one of claims 1 to 6.

8. The polystyrene-based hard carbon microspheres according to claim 7, characterized in that: The average particle size of the polystyrene-based hard carbon microspheres is 3 to 15 μm; Preferably, the compacted density of the polystyrene-based hard carbon microspheres is 1.1 to 1.6 g / cm 3 ; Preferably, the specific surface area of ​​the polystyrene-based hard carbon microspheres is 2 to 25 m 2 / g; Preferably, the crystallite interlayer spacing of the polystyrene-based hard carbon microspheres is 0.374-0.421 nm.

9. An electrode material, characterized in that: The electrode material comprises the polystyrene-based hard carbon microspheres according to any one of claims 7 or 8.

10. Use of the electrode material according to claim 9 in lithium ion batteries or sodium ion batteries.

Citation Information

Patent Citations

  • Spherical hard carbon lithium ion battery cathode material and preparation method thereof

    CN102386384B

  • A hard carbon material, its preparation method, and a sodium-ion battery

    CN112397715B

  • Method for preparing monodisperse carbon microsphere with controllable configuration

    CN101555008A

  • Spherical particles comprising carbon nanomaterial graft polymer and methods of making and using same

    CN115353745A

  • Carbon material, negative electrode used for lithium-ion secondary cell and lithium-ion secondary cell

    CN1337752A